The early clinical phenotype of Fabry disease: a study on 35 European children and adolescents - Ries, Markus; Ramaswami, Uma; Parini, Rossella; Lindblad, Bengt; Whybra-Trümpler, Catharina; Willers, Ingrid; Gal, Andreas; Beck, Michael (European journal of pediatrics, 2003)
Fabry disease (FD) is a debilitating progressive multisystem X-linked lysosomal storage disorder. It was generally believed that the disease affects only adult males. Through systematic pedigree analysis, we identified 35 paediatric FD patients (age 1 to 21 years, mean 12.6 years) in 25 families. Predominant signs in this cohort were: acroparesthesia, hypohidrosis, and cornea verticillata. Neurological and psychological changes, such as tinnitus, recurrent vertigo, headache, diminished level of activity, fatigue, and depression were often observed. Angiokeratoma and gastrointestinal symptoms were frequent. Some patients also showed cardiac abnormalities. Six children and adolescents (three males and three females) over 14 years of age had renal involvement (all with proteinuria, one male had a decreased creatinine clearance of 62 ml/min). No males, but three females (1.5, 4 and 9 years of age), were free of signs and symptoms. Males (n=15, age 1 to 21 years, mean 12.4 years) and females (n=20, age 1.5 to 20 years, mean 12.7 years) showed comparable disease severity. However, the clinical courses demonstrated a wide intra- and interfamilial variability and tended to be more heterogeneous in the girls. Female patients are frequently affected at an early age, not much differently than males. They should be carefully examined because most carriers are symptomatic. Conclusion: Fabry disease usually becomes clinically manifest in childhood. Renal involvement can begin in adolescence. The diagnosis is made following a high level of suspicion or systematic pedigree analysis. It is crucial for paediatric Fabry disease patients to have early access to optimal supportive symptomatic management. Enzyme replacement therapy has shown promising effectiveness in adults. Considering its widespread therapeutic and potential preventive benefits, enzyme replacement therapy should be initiated at an early stage, prior to the onset of irreversible complications.
Gesehen am 16.05.2019